The Effect of the Quality of Public Transportation Services on the Interest of Jakarta Tourism Visits - Euis Komalawati; Febriyanti Angelina (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to determine the influence of the quality of public transportation mode services on the Interest of tourist visits in DKI Jakarta. The mode of transportation in question is the Jakarta Explorer Tour Bus service in DKI Jakarta. This study used quantitative methods with a sample of 100 users of public transportation modes. The results showed service quality's influence on tourist visits' Interest with a regression equation of Y = 16.747 + 0.577X. Based on the hypothesis test, the calculated t value of 7,781 > t table is 1.984 and the value (Sig) of 0.000 < 0.05, which means that the service quality variable (X) has a significant effect on the tourist attraction variable (Y) with a coefficient of determination value (R2) of 0.382, it shows that the Quality of Service (X) of Tourism Visiting Interest (Y) is 38.2%.